(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Service companies always working to increase their competitiveness and efficiency of the survival, growth and development in the present and the future, including insurance companies, so as to increase competition, especially after the emergence of the civil companies dramatically after 2003, has become the goal of recent studies carried out by the organizations is the human capital, because its success and excellence and achievement its objectives depends on the human, and this does not mean that the other components are not important, but also rely on the rights which has increased interest in the search for the way in which they can guide the behaviors and values ​​and their own language in line with the organization’s strategy and goals intending to access them, and here became behavior Humanitarian most effective means in the customer to achieve competitive advantage. The researcher has to choose a sample of (100) Single of the general insurance companies, has been the use of the questionnaire as a means to gather information, and test research hypotheses, which focused on the existence of the relationship and impact between human behavior and competitive advantage, then the data was obtained through the search tool using analysis a number of statistical tools to get to the results, the most important (mean, standard deviation, and testing of T, and the coefficient of simple correlation, and regression analysis).